Aplikasi Pupuk Organik Cair Daun Gamal Menggunakan Trichoderma harzianum Terhadap Pertumbuhan dan Hasil Tanaman Terung Ungu - Khairunanissa Khairunanissa; Akhmad Rizali; Noor Khamidah (Agroekotek View, 2019)
The manufacture of poc use leaves gamal use the application of trichoderma harzianum in order to increase the pace of growth the limb of the results of a plant eggplant purple.This study using random design complete single factor consisting of Tu0: without granting, poc Tu1 poc: leaves gamal 40ml/l water, Tu2 poc: leaves gamal 80ml/l water and poc Tu3 leaves gamal 120ml/l water. Research parameters observed in form of higher plants (cm); number of leaves (strands); the number of flowers (fruit); the number of fruit (fruit) and heavy fruit (g). Based on research that has been obtained the provision of poc leaves gamal by fermentation trichoderma harzianum with highest dose of 120ml/l water able to give increased the result in higher plants, the number of, leaves the number of heavy fruit eggplant. interest as well a doses of 120ml / l is not able to increase the number of fruit on plant eggplant on the research has been implemented.